Designing a compact language book in learning Arabic for Islamic banking and finance - Sahrir, Muhammad Sabri; Zainuddin, Nurkhamimi (s.n, 2012)
This research aiming at producing a manual compact of language learning in Arabic among staff, managers and practitioners in the sector of Islamic banking and finance, as a part of research in designing Arabic language intensive course for special and business purposes